2017
DOI: 10.1002/ijc.30884
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal risk factors for testicular cancer: The EPSAM case–control study

Abstract: Testicular cancer is considered to originate from an impaired differentiation of fetal germ cells, but puberty could represent another time window of susceptibility. Our study aimed at investigating the association between environmental exposures acting during puberty/adolescence (13-19 years of age) and the risk of testicular cancer. We used data of the EPSAM study, a case-control study on germ-cell testicular cancer conducted in the province of Turin, Italy, involving cases diagnosed between 1997 and 2008. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…However, not all publications support the connection between tobacco use and testicular cancer. A recent Italian study reported no apparent association between alcohol or tobacco use during adolescence (ages 13-19 years) and later diagnoses of testicular cancer (40). Maternal smoking during pregnancy may lead to elevated rates of cryptorchidism in male offspring, which is a known risk factor for the future development of testicular cancer.…”
Section: Cancer Risk Among Infertile Men Testis Cancermentioning
confidence: 98%
“…However, not all publications support the connection between tobacco use and testicular cancer. A recent Italian study reported no apparent association between alcohol or tobacco use during adolescence (ages 13-19 years) and later diagnoses of testicular cancer (40). Maternal smoking during pregnancy may lead to elevated rates of cryptorchidism in male offspring, which is a known risk factor for the future development of testicular cancer.…”
Section: Cancer Risk Among Infertile Men Testis Cancermentioning
confidence: 98%
“…The relative risk of TGCT was 2.23 even if patients underwent orchiopexy before 13 years old (27). Moirano et al (28) observed that undescended testis was higher in TGCT group (11.4%) than in healthy control group (3.0%). Hanson et al (29) detected an increased risk of testicular cancer (hazard rate of 3.3) in subfertile men when compared with fertile men (29).…”
Section: Discussionmentioning
confidence: 98%
“…The study population has been previously described [ 23 , 24 ]. Between 2008 and 2010, a population-based case-control study was conducted among testicular cancer patients diagnosed in the Province of Turin, Italy, between 1997 and 2008.…”
Section: Methodsmentioning
confidence: 99%